1999
DOI: 10.1101/gad.13.24.3280
|View full text |Cite
|
Sign up to set email alerts
|

A cis-acting element in the 3'-untranslated region of human TNF-alpha mRNA renders splicing dependent on the activation of protein kinase PKR

Abstract: We report a role for the 3-untranslated region in control of mRNA splicing and show that human TNF-␣ 3 UTR harbors a cis-acting element that renders splicing of precursor transcripts dependent on activation of PKR, the RNA-activated protein kinase that phosphorylates eukaryotic initiation factor 2 (eIF2). When this element, designated 2-APRE, is present, splicing becomes sensitive to inhibition by the PKR inhibitor, 2-aminopurine, or by coexpression of transdominant-negative mutant PKR. Our results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 53 publications
3
125
0
Order By: Relevance
“…After transcription, pre-mRNA is processed through a series of RNA splicing events. In a most recent study, an element in the 3'-UTR of tumor necrosis factor a mRNA was found to render this RNA processing mechanism (Osman et al, 1999). After that, mRNAs are to be exported out from the nucleus through the nuclear pore.…”
Section: Discussionmentioning
confidence: 99%
“…After transcription, pre-mRNA is processed through a series of RNA splicing events. In a most recent study, an element in the 3'-UTR of tumor necrosis factor a mRNA was found to render this RNA processing mechanism (Osman et al, 1999). After that, mRNAs are to be exported out from the nucleus through the nuclear pore.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether 2-AP can interfere with the stress-induced stabilization of p53, we pretreated wild-type (wt) p53-containing NIH 3T3 cells with 10 mm 2-AP or solvent only for 2 h and then exposed the cells to AD, UV, or g-radiation for various lengths of time. This concentration of 2-AP was shown to induce its observed cellular effects (Andreassen and Margolis, 1992;Jarrous et al, 1996;Strong et al, 1998;Osman et al, 1999). Within 1 h after addition of AD in the absence of 2-AP, the protein level of p53 increased when compared to that of the cells without AD treatment (Figure 1a).…”
Section: Dna Damage-induced P53 Accumulation Is Compromised In the Prmentioning
confidence: 94%
“…PKR is a Ser/Thr kinase expressed constitutively at low levels in most cells but is induced by viruses, dsRNA, and IFN (Kaufman, 2000). 2-AP prevents the establishment of the antiviral state in IFNtreated cells (Wathelet et al, 1989) and has been instrumental in several functional studies of PKR, such as elucidating the ability of PKR to regulate the expression of tumor necrosis factor-a gene (Jarrous et al, 1996;Osman et al, 1999), the activation of transcription factor NF-kB (Cheshire et al, 1999), or explaining the role of PKR in reovirus-mediated oncolysis of tumor cells (Strong et al, 1998). Our previous studies correlated the absence of wt PKR function with downregulation of two p53 downstream targets, p21 and mdm2 genes and a partial reduction of stress-induced p53 phosphorylation on serine 18 (Cuddihy et al, 1999a).…”
Section: ------------------------"mentioning
confidence: 99%
See 2 more Smart Citations